The economics of user-generated content : impacts on consumer decision-making and consumption - Zhang, Yimiao (2019)
Nowadays, many of the online content is user-generated content. User-generated content is any type of content created and published by unpaid contributors (end users) mainly on social media platforms or on e-commerce platforms and is read, viewed, or consumed by other end users of the platforms. User-generated content may be in various formats, for example images, videos, blog posts, and online reviews. Users create user-generated content for many purposes, for instance, sharing daily life, making comment towards certain event or product/brand, and sharing some useful information to others. The importance of user-generated content comes from the economic value it creates by attracting users’ attention to consume the content and further shaping users’ believe to make decisions. For example, sharing useful information in a video or in a blog post may attract a lot of audience and readers such that the traffic to the content may be converted to money in various ways such as advertisement income and readers’ direct reward. Endorsing or critiquing a product in a blog-post or in an online review may affect other consumers’ purchase decision or change of decision. Therefore, it is essential for us to understand the drivers and outcomes of consumption of user-generated content under different situations. In this thesis, we conducted two studies to examine the drivers as well as outcomes of user-generated content consumption in different empirical settings. Study 1 examined the drivers of continued consumption of user-generated content (online videos) and study 2 examined the outcomes of consumption of user-generated content (online reviews) in regard to consumer attitude change. In study 1 (chapter 1), we examine the impact of user-generated content features on the continued consumption of the content from a dynamic perspective. Specifically, we use YouTube as the empirical setting to examine what are the factors that sustain attention of individuals in this information economy. We situate our study in an empirical context and hope to unpack the psychological underpinnings which lead to greater focus and attention. We apply theory of optimal stimulation level (OSL) to explore why users stay on with particular user-generated content. The results reveal that consistency in conversation pace and variety in content topic are positively related to sustained attention. In study 2 (chapter 2), we refer to theory in psychology and marketing to explore the impact of consumer online review on consumer post-purchase attitude change. Using a proprietary dataset from hotel industry and public user-generated online reviews, we examine how the numeric and textual information of post-purchase review affect hotel room cancellation behavior. The results show negativity bias and different trust levels on hedonic and utilitarian comment when consumers make post-purchase decision. This thesis contributes to user-generated content literature from two perspectives. Firstly, we point out content features that affect users’ continued consumption of user-generated content from a dynamic perspective in the social media context. Secondly, we explore the impact of consumption of user-generated online review on consumer post-purchase attitude change. We believe this thesis also has important practical implications for the design of user-generated content and for the management of user-generated online review.